A Descriptive Study Of Community Awareness Regarding Ambulance Service Request Mechanisms In Emergency Situations (The Review of Diabetic Studies, 2025)
This descriptive study aims to assess the level of community awareness regarding the mechanisms for requesting ambulance services during emergencies. The proper use of ambulance services is a crucial factor in reducing injury and mortality rates, especially when timely intervention can significantly impact patient outcomes. However, previous reports have indicated that many individuals lack sufficient knowledge about when and how to seek emergency medical assistance, leading to either delayed responses or misuse of emergency systems. The study explores the community's understanding of appropriate channels for contacting ambulance services, the types of emergencies requiring immediate medical intervention, and the basic steps expected of a caller reporting an incident. Data are collected using a structured questionnaire targeting different demographic groups to identify gaps in awareness and patterns related to age, education, and prior experience with emergency services. The study's findings are expected to contribute to improving public health policies, enhancing community training programs, and boosting the efficiency of emergency medical systems. The recommendations will emphasize the need to organize educational campaigns to promote the optimal use of ambulance services.